Performance of SARS-CoV-2 Antigen-Detecting Rapid Diagnostic Tests for Omicron and Other Variants of Concern - Raïch-Regué, Dàlia; Muñoz-Basagoiti, Jordana; Perez-Zsolt, Daniel; Noguera-Julian, Marc; Pradenas, Edwards; Riveira-Muñoz, Eva; Giménez, Neus; Carabaza, Assumpta; Giménez, Francesc; Saludes, Verónica; Martró, Elisa; Robert, Neus; et al. (Frontiers in Microbiology, 2022)
The SARS-CoV-2 antigen-detecting rapid diagnostic test (Ag-RDTs) is an easy-to-use diagnostic tool to identify the contagious individuals and reduce the new infections. However, to be effective, Ag-RDTs require the detection of distinct variants of concern (VOC) with high analytical sensitivity. Here, we found that the VOC diverge at the nucleocapsid protein used by four commercial Ag-RDTs for the viral detection. Relative to the original D614G variant, there was a 10-fold loss of detection for the Delta and Alpha variants in certain Ag-RDTs, a reduction above the threshold required to isolate the viable virus. However, Beta and Omicron variants did not lose the detection capacity. As the new VOC arise, successful contact tracing requires continuous monitoring of Ag-RDTs performance.